iDXA, Prodigy, and DPXL dual-energy X-ray absorptiometry whole-body scans: a cross-calibration study - Hull, Holly (2008)
PURPOSE: Total body fat, lean, and bone mineral content (BMC) in addition to regional fat and lean mass values for arms, legs, and trunk were compared across a pencil-beam (Lunar DPX-L) and two fan-beam (GE Lunar Prodigy and GE Lunar iDXA) dual energy x-ray absorptiometry (DXA) systems. METHODS: Subjects were a multi-ethnic sample of 99 healthy adult males (47%) and females (mean ± SD: age 46.3 ± 16.9 yrs; weight 73.4±16.6 kg; height 167.6±9.7 cm; BMI 26.0±5.2 kg/m(2)) who had whole-body scans performed within a 3 hour period on the three systems. Repeated measures ANOVA was used to test the null hypothesis that the mean values for the three systems were equal. Translation equations between the methods were derived using regression techniques. RESULTS: BMC: For both genders, total BMC by iDXA was lower (P≤0.004) than the other systems. Lean: For males, iDXA was lower (P≤0.03) than the other systems for total, trunk and arms. For females, DPXL estimated higher (P<0.001) lean mass compared to the other systems for total, trunk and arms, but iDXA estimated greater legs lean mass. For both genders, all DPXL mean values were greater than Prodigy mean values (P<0.001). Fat: In females, all 3 systems were different from each other for total, trunk, and legs (P≤0.04). For arms, DPXL and iDXA were higher than Prodigy (P<0.0004). For males, DPXL was less (P<0.001) for total body, trunk and legs compared to the other two systems and greater than Prodigy only for arms (P<0.0007). These data were used to derive translation equations between systems. For several measurements, the differences between systems were related to gender. CONCLUSION: For estimation of BMC and body composition, there was high agreement between all DXA systems (R(2)=0.85 to 0.99). Even so, cross-calibration equations should be used to examine data across systems to avoid erroneous conclusions.